Meningkatkan Hasil Belajar IPS melalui Penerapan Kuis Interaktif Berbasis Teknologi Siswa Kelas 8 SMPN 1 Barru - Muhammad Nawir; Aini Nurpratiwi; Dimas Mulyadin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study was conducted because of the lack of interest in learning the IPS subject of grade IX junior high school which according to the students always makes them sleepy. The low interest in learning students can be seen from the minimal participation in class discussions and the lack of motivation to complete assignments. To overcome this, learning innovation was carried out by utilizing Game Based Learning Quizizz, an interactive quiz platform based on gamification that can increase student motivation. This study aims to test whether the use of Quizizz can increase students' interest in learning in IPS. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages, with 31 subjects of grade IX students of SMPN 1 Barru. Data were collected through observation, questionnaires, and interviews, then analyzed descriptively qualitatively and quantitatively. The results showed that the use of Quizizz significantly increased students' interest in learning. In Cycle 1, there was an increase in interest in learning, although some students still had difficulty using the application and many were still not interested and lacked learning. After improvements in Cycle 2, 90% of students became more active and enthusiastic, supported by interview results which showed that students felt more motivated and enjoyed learning through interactive quizzes because they could see their scores directly using the LCD.